1985
DOI: 10.1099/00221287-131-2-295
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Gene for Glucan-binding Protein from Streptococcus mutans in Escherichia coli

Abstract: The structural gene for a glucan-binding protein (GBP) of Streptococcus mutans has been inserted into a bacteriophage A vector and expressed in Escherichia coli K12. Lysates of E. coli infected with the recombinant phage contain an antigenic protein of the same size as S . mutans GBP. The GBP synthesized in E. coli can be affinity-purified on immobilized glucan and antiserum raised against it has been shown to precipitate fructosyltransferase activity from S . mutans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 12 publications
4
48
0
1
Order By: Relevance
“…GbpA was originally isolated by Russell (1979) and designated GBP (Douglas and Russell, 1982;Russell et al, 1985). Several years later, Smith et al (1994) reported the isolation of GbpB.…”
Section: S Mutans Gbpsmentioning
confidence: 99%
“…GbpA was originally isolated by Russell (1979) and designated GBP (Douglas and Russell, 1982;Russell et al, 1985). Several years later, Smith et al (1994) reported the isolation of GbpB.…”
Section: S Mutans Gbpsmentioning
confidence: 99%
“…Streptococcus mutans GS-5, serotype c (Bratthall, 1970) and transposon-generated auxotrophs of S. niutans GS-5 (Procino et al, 1988) were grown in Todd-Hewitt broth (Difco) Smorawinska et al (1983); gbp, Russell et al (1985); gtfA, Robeson et al (1983); gtfB, Aoki et al (1986); g t f c , Hanada & Kuramitsu (1988); gtfD, Hanada & Kuramitsu (1989); ldh, Hillman et al (1990); pac, Lee et al (1988), Okahashi et al (1989);scrA, Sat0 et al (1989); scrB, Hayakawa et al (1986), Lunsford & Macrina, (1986; wapA, Ferretti et al (1989). DNA isolation.…”
Section: Methodsmentioning
confidence: 99%
“…All tests were performed in triplicate. To confirm the data obtained from the RPLA assays, 50% of the septicaemia and nasal isolates were tested for production of enterotoxins A, B, C, and D by Western immunoblotting (Burnette, 1981) with specific rabbit anti-enterotoxin sera (Russell et al, 1985) and 50-fold concentrated culture supernate proteins, as described by Coleman et al (1986). In a similar fashion, all isolates which were TSST-1-positive (TSST-1 +), as determined by RPLA assays, were re-tested for TSST-1 production by immunoblotting with specific rabbit anti-TSST-1 serum.…”
Section: Detection Of S Aureus Enterotoxins and Toxic Shock Syndrommentioning
confidence: 99%